The role of waqf investment funds in achieving sustainable development - Abulatifa, Mohammed Maher Awad; Hasan Saleh, Abdulmajid Obaid; Mohd Noor , Azman (International Journal of Al-Turath In Islamic Wealth and Finance, 2023)
The research aims to demonstrate the role of WAQF investment funds in achieving sustainable development, through support in the economic, educational, health and other fields that contribute to achieving sustainable development to preserve, develop and develop current assets to last as long as possible and serve the largest number of generations, The investigators used the descriptive approach in all data, analyzing and describing them to reach the results of the study, the most important of which is that waqf investment funds have a major role in eradicating poverty and achieving sustainable development for society in various fields, and waqf investment funds are considered a product that achieves sustainable development for endowments. The research recommended the need to activate the waqf investment funds model in all countries because it contributes to the production of endowment financial power that greatly helps in achieving sustainable development, as well as making strategic plans for the work of these funds to benefit from them for a longer period.